2012
DOI: 10.1139/h11-152
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between the playing position of soccer players and their food and macronutrient intake?

Abstract: Many authors have proposed the necessity of the design and implementation of dietary and nutrition education programs for soccer players, although little information is available about the determinants of food selection and nutrient intake. The aim of this study was to evaluate the nutritional intake and eating patterns of soccer players according to their playing position in the team. Eighty-seven young male soccer players (aged 16-21 years) were recruited from the junior teams of a Spanish First Division Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 42 publications
4
45
1
Order By: Relevance
“…The results of this study revealed wide differences in energy intake, ranging from 2209 to 3259 kcal, as was already described for players (Iglesias-Gutiérrez et al, 2012;Maughan, 1997;Noda et al, 2009). It is recognised that dietary records of athletes are prone to error information mostly through under-reporting (Magkos & Yannakoulia, 2003), which can compromise the interpretation of dietary data.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results of this study revealed wide differences in energy intake, ranging from 2209 to 3259 kcal, as was already described for players (Iglesias-Gutiérrez et al, 2012;Maughan, 1997;Noda et al, 2009). It is recognised that dietary records of athletes are prone to error information mostly through under-reporting (Magkos & Yannakoulia, 2003), which can compromise the interpretation of dietary data.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, Ono and colleagues reported it to be difficult for football players to follow a diet rich in carbohydrates (Ono, Kennedy, Reeves, & Cronin, 2012). We were expecting that the higher physiological requirements for main referees could have led to an increased spontaneous intake of carbohydrates compared with the assistant referees, resembling the findings described in players with different playing positions (Iglesias-Gutiérrez et al, 2012). However, we did not find any significant difference on carbohydrates intake between main and assistant referees (4.0 ± 0.7 g · kg −1 and 4.1 ± 0.9 g · kg −1 , respectively), perhaps because their training regimes didn't differ a lot.…”
Section: Discussionmentioning
confidence: 75%
“…As it has been proposed that sleep parameters may be affected as a result of a greater need for recovery sleep due to more demanding workloads [44], it may be hypothesised that players in a more 'physically' demanding position (i.e. fullbacks, midfielders and forwards [45,46]) may exhibit positional differences in sleeping patterns compared with goalkeepers and central defenders.…”
Section: High-intensity Exercise and Sleepmentioning
confidence: 99%
“…We previously reported that the food intake of young male soccer players is derived from the following food groups: cereals, derivatives, and potatoes; milk and dairy products; meat, poultry, and derivatives; and oil; which together provided 65% of total daily energy intake, with a marginal contribution from vegetables and fruits [43]. …”
Section: Nutritional Intake and Eating Habits Of Soccer Playersmentioning
confidence: 99%
“…However, the majority of studies conducted have revealed inadequate nutritional intake in both male and female soccer players [38,39,40,41,42,43,44,45,46,47], underscoring the need to improve short and long-term adherence to these recommendations. While there is unanimous agreement on the need to design and implement nutrition-specific intervention programs for soccer players, there is a paucity of information on the eating habits and correlates of nutritional behavior of soccer players.…”
Section: Introductionmentioning
confidence: 99%